Critiquing War in the Classroom: Problematizing the Normalization of Gendered Militarism - Nancy Taber (Adult Education Research Conference, 2011)
This paper describes an analytic autoethnographical research study focusing on experiences developing, delivering, and evaluating course content critiquing war from a feminist anti-militarist perspective. It discusses the difficulty of challenging societal notions as relates to gendered militarism in post- secondary classrooms at undergraduate, graduate, and postgraduate levels. Thematic findings from the research include: professional vulnerability, student resistance, pedagogical possibility, and scholarly holism. This research demonstrates the importance of not only interrogating the educational experiences of post-secondary professors, but of connecting them to complex sociocultural educational issues related to war, militarism, and gender.
Keywords: autoethnography; feminist antimilitarism; post-secondary; war